Kewenangan Kepala Desa Dan Camat Dalam Pembuatan Surat Keterangan Ahli Waris - Rayhan Isha Mahendra; Dominikus Rato; Dyah Octhorina Susanti (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Certificate of heirs which generally only contains information and statements from the heirs that they are truly the legal heirs of the deceased testator. Certificate of heirs issued by the Village Head and Sub-district Head as a basis for determining the heirs who are entitled to an inheritance. In practice, Certificates of Heirs issued by the Village Head and Sub-district Head in legal acts made by notaries often cause problems and disputes. The type of research used in this study is normative juridical with a statute approach and a conceptual approach. Law Number 32 of 2004 concerning Regional Government does not explain in detail the authority of the Village Head and Sub-district Head to know or confirm certificates of inheritance made by Indonesian heirs. Certificate of inheritance rights or certificate of inheritance rights or certificate of heirs, whether made by themselves through a statement by the heirs or made directly through a statement by the Village Head and Sub-district Head, in principle has legal force as evidence in the case of transfer of land rights due to inheritance as long as the certificate of inheritance rights is made legally and all legitimate heirs are included in the certificate of inheritance rights. Certificates of heirs made by the Village Head and Sub-district Head can be classified as private deeds. The position of the certificate of heirs as evidence issued by the Village Head and Sub-district Head in principle has legal force as evidence of a letter.